Female leadership for sustainability: green, cultural and social impact of the world's best sportswomen - Torres Mancera, Rocío (European Public & Social Innovation Review, 2025)
Introduction: Female activism and social responsibility seem to be unnoticed but carries a profound impact on community, business, and green legacy. This research aims to analyze the digital communication practices and ethical initiatives of worldwide top female athletes, with a focus on their international brand image. By studying their online presence and engagement, we will explore convergences and divergences between genders in terms of talent revenue and personal branding. Methodology: Our work provides insights into how these sportswomen interact on the internet-based landscape, their approaches to global leadership, and the causes they support. The applied methodology involves a comparative analysis of top athletes by gender and categories to contrast diversity. Statistical techniques, including ANOVA and regression analysis, are employed to examine the data and derive meaningful insights, finding their remarkable influence beyond their exceptional performance in sports. Results: Sportswomen harness the power of online visibility as a strategical tool to amplify their influence and drive social change, leveraging their talent to go beyond the economic returns of their professional performance. Discussions and findings: The current study discloses how sportspeople serve as role models, exhibiting good practices and leading by example to benefit the community. Their dedication to sustainability, both in terms of people's well-being and the preservation of our planet for future generations, is evident in their actions. Their brand image transcends their athletic achievements, reflecting their commitment, responsibility, and entrepreneurship towards the interests of the community. Their influence extends far beyond the surface, leaving a lasting and positive effect on stakeholders.